Multiband Ultrathin Polarization-Insensitive Terahertz Perfect Absorbers With Complementary Metamaterial and Resonator Based on High-Order Electric and Magnetic Resonances - Xiutao Huang; Conghui Lu; Cancan Rong; Zhaoyang Hu; Minghai Liu (IEEE Photonics Journal)
Terahertz perfect metamaterial absorbers (PMA) based on higher order resonances have exhibited important applications in detecting, sensing, and imaging. However, most of them suffer from polarization and incident-angle dependence due to their asymmetrical structure. Here, we numerically investigate a kind of ultrathin triple-band PMA with polarization stability and wide angle of incidence. Numerical results reveal that three resonance peaks with nearly 100% absorptivity are obtained at 1.605, 4.425, and 4.946 THz under different polarization angles. It is interestingly found that the absorptance of two higher order resonances is inversely increased when the size of the middle dielectric spacer is smaller. The three resonance peaks in transverse electric and transverse magnetic modes nearly maintain fixed for oblique incidence up to 60°. Importantly, another four-band and dual-band perfect absorptions are easily achieved by a complementary method without doing iterative numerical simulation. The complementary metamaterial based absorber reaches more than 98% absorptance at four resonance frequencies. The metamaterial absorber based on complementary resonator also obtains two absorption peaks at 2.65 and 5.84 THz.